UPAYA PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN RODA PINTAR SISWA KELAS I SEKOLAH DASAR - Aidah, Aidah; Amalia, Arsyi Rizqia; Nurasiah, Iis (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to improve early reading skills of first-grade students in elementary school through the use of the Smart Wheel media. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart spiral model, consisting of planning (plan), implementation (act), observation (observe), and reflection (reflect) stages, conducted over two cycles with two actions per cycle. The study involved 30 students as subjects. Data were collected through observation and tests. The success indicator was reaching a minimum mastery criterion (KKM) of 80%. The results showed that the average pre-cycle test score was 67, categorized as low. In the first cycle, the average increased to 75, categorized as sufficient. In the second cycle, the highest score reached 85, categorized as good. The study was stopped as 85% of students (25 students) achieved mastery while 17% (5 students) had not yet met the criterion. It can be concluded that the implementation of Smart Wheel media effectively enhances students’ early reading skills.